Nutrition and pregnancy. - Gonzales Del Riego, Manuel (2015)
As it can be assumed, regular nutrition is one of the pillars of growth and human development. When this contribution is in deficit by quality or quantity or may not be properly exploited, it affects the development process and increases the risk of health damage. Similarly, if the contribution is excessive, transcendental metabolic disturbances occurs.